A new investigation on biological activities and potential health functions of royal jelly on Saccharomyces cerevisiae - Beyaz, Seda; Gok, Ozlem; Aslan, Abdullah (Progress in Nutrition, 2022)
Study Objective: Royal jelly is a bee product that has a nutritious value and has been used in the treatment of many diseases since ancient times. Royal jelly has the ability to scavenge free radicals thanks to its antifungal, antiviral, antimicrobial, anti-inflammatory and antioxidant effects. Methods: In this study, four groups were created to investigate whether Royal jelly has a protective role against copper chloride (CuCl2) damage in Saccharomyces cerevisiae. Study groups: (1) Control Group: Group in which only yeast was cultivated; (2) CuCl2 Group: the group given CuCl2 (30 mM); (3) Royal Jelly Group: The group given Royal jelly (10%); (4) Royal Jelly + CuCl2 Group: The group given Royal jelly (10%) + CuCl2 (30 mM). Saccharomyces cerevisiae cultures were grown at 30 °C for 1, 3, 5 and 24 hours. Cell growth, GSH (glutathione) levels, CAT (catalase) activities and lipid peroxidation MDA (malondialdehyde) analyzes were determined by spectrophotometer. Total protein concentrations were determined by SDS-PAGE electrophoresis and Lowry protein method. Results: when compared with the CuCl2 group, cell growth (1, 3, 5 and 24 hours), total protein synthesis and GSH level (24 hours) increased in Royal jelly groups, while MDA level (24 hours) decreased. Conclusions: Thanks to the antioxidant properties of Royal jelly, it has been determined that it increases cell growth and total protein synthesis by reducing oxidative stress in Saccharomyces cerevisiae culture. It has been concluded that these natural products also have strong therapeutic effects in the treatment of many diseases.